2011
DOI: 10.1111/j.1365-2230.2010.03962.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Staphylococcus aureus colonization in patients with atopic dermatitis in Sri Lanka

Abstract: SA colonization rates were significantly associated with increasing age and severity of AD, and particularly with duration of lesions. Patients with severe disease were also more likely to be colonized with SA strains resistant to conventional antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 25 publications
2
13
1
4
Order By: Relevance
“…Although only a small percentage of the general population has been reported to be either colonized or infected by the bacteria, the prevalence increases to up to 90% in patients suffering from atopic skin disease (Goh et al, 1997;Chiu et al, 2009;Gomes et al, 2011). First, Strange et al (1994) observed KC-mediated activation of allogeneic T cells in the presence of IFN-g and staphylo-enterotoxin B that was reduced by the addition of HLA-DR antibodies.…”
Section: Direct Activation Of Antigen-specific T Cellsmentioning
confidence: 92%
“…Although only a small percentage of the general population has been reported to be either colonized or infected by the bacteria, the prevalence increases to up to 90% in patients suffering from atopic skin disease (Goh et al, 1997;Chiu et al, 2009;Gomes et al, 2011). First, Strange et al (1994) observed KC-mediated activation of allogeneic T cells in the presence of IFN-g and staphylo-enterotoxin B that was reduced by the addition of HLA-DR antibodies.…”
Section: Direct Activation Of Antigen-specific T Cellsmentioning
confidence: 92%
“…Interventions to reduce Staphylococcus aureus in the management of atopic eczema: an updated Cochrane review. Br J Dermatol 2010;163: [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Scientific Summary Backgroundmentioning
confidence: 99%
“…21,23 Furthermore, more severe eczema is associated with higher densities of the organisms 21,23,24 and more resistant strains. 25 There is evidence that a number of factors contribute to this propensity for colonisation and infection, including dysregulation of the adaptive immune response, reduced antimicrobial peptide levels, diminished recruitment of cells to the skin, toll-like receptor defects and epidermal barrier abnormalities. 26 The exact role of S. aureus in the maintenance or exacerbation of eczema is not clear.…”
Section: Infected Eczemamentioning
confidence: 99%
“…However, the benefit of antibiotic use in AD is still disputed with a Cochrane review presenting studies showing no significant difference in global outcome for clinically infected eczema when oral antibiotics were compared with placebo or when topical steroid antibiotic combinations were compared with steroid alone [50]. Given the contradictory results available, it would be prudent to be restrictive in prescribing antibiotics, mainly because of an increasing resistance problem worldwide [55, 56, 57, 58]. …”
Section: The Rationale For Antiseptic Use In Atopic Eczemamentioning
confidence: 99%